Bandwidth Variation of Photonic Muliple Quantum Well under Polarized Incidence of EM Wave - Maity, Avisek; Deyasi, Arpan; Chottopadhyay, Barnisa; Banerjee, Usmita (2014 International Conference on Devices, Circuits and Communications (ICDCCom), 2014)
Optical bandwidth of photonic multiple quantum well structure is analytically computed subject to the polarized incidence of electromagnetic wave on the structure. Both p-polarization (TE mode) and s-polarization (TM mode) are considered to observe the tuning of bandwidth by suitable variation of structural parameters. Semiconductor heterostructure is considered as material system for simulation purpose, and result is compared with conventional SiO 2 -air system with similar dimensional and material configurations. Comparative study reveals the fact that better tuning in optical domain can be achieved with semiconductor system, which speaks about its supremacy over conventional system. Result is important for application of the structure in photonic integrated circuit.